Synthesis of 2,7-diarylpyrazolo [1,5-a] pyrimidine derivatives with antitumor activity. Theoretical identification of targets - Andrés Ballesteros-Casallas; Margot Paulino; Pietro Vidossich; Carol Melo; Elizabeth Jiménez; Juan-Carlos Castillo; Jaime Portilla; Gian Pietro Miscione (Elsevier, 2022)
The pyrazolo[1,5-a]pyrimidine ring system constitutes a privileged scaffold for developing drug-like compounds, whose biologic activity is dictated by the nature and position of the substituents on the heterocyclic core. Herein, we report the synthesis of nine 2,7-diarylpyrazolo[1,5-a]pyrimidine derivatives and the assessment of their antitumor activity against a colorectal carcinoma cell line. Four compounds showed substantially impaired cell viabilities. We carried out a virtual reverse screening campaign to identify their biological targets. The results showed that many putative targets had been related to cancer, particularly colorectal carcinoma, which supports the computational strategy. The structural and physicochemical information available for the complexes between active compounds and identified targets offers the opportunity to design new derivatives, which optimize interactions and improve the binding energy.